PERKEMBANGAN ENZIM PENCERNAAN LARVA IKAN PATIN, Pangasius hypophthalmus sp. - Irzal Effendi; . Widanarni; D. Augustine (Jurnal Akuakultur Indonesia)
Development of digestive enzymes; protease, lipase and amylase were observed in patin catfish, Pangasius hypophthalmus, larvae.  The 1 day old larvae (day after hatching), with 3,37-3,97 mm length and 0,62-0,79 mg weight, were reared in aquarium 60x50x40 cm with stocking  density of 20 fish/l.  Larvae were fed  Artemia dan tubificid worms 2-8 dan 7-15 days after hatching (dAH),  respectively (schedule I);  2-6 and  5-15 dAH (schedule II); and 2-4 and 5-15 dAH (schedule III).  Chlorella was ready to eat by larvae at the entirely rearing.  For enzyme assay, larvae were sampled from each aquarium at stages of 1, 2, 3, 5, 7, 10 and 15 dAH.    Protease and lipase activity were detected in digestive tract of  1 dAH larvae.   Digestive enzymes development have a similar pattern in larvae for all feeding schedules.  Protease activity  decreased with the increasing of age until 3 dAH, then increased  until the larvae reached 7 dAH, and sharply decreased until 10 dAH and then slowly decreased thereafter. Lipase activity tended to increase slowly with age up to 3 dAH, and increased sharply until 5 dAH, and then decreased sharply until 7 dAH  before decreased again up to the end of rearing.  Amylase activity in larvae increased slowly with the increasing of age up to 5 dAH, then increased sharply until 7 dAH, and decreased thereafter.  In dimly lighted larvae, amylase activity decreased before increased up to 12 d AH, then decreased thereafter.  The amount of food organisms in larval gut, body weight and length, and survival rate of larvae were also measured and discussed. Key Words:  Digestive enzymes, development, larvae, patin catfish, Pangasius hypophthalmus